IMPLEMENTASI REDUKSI NOISE PADA CITRA ULTRASONOGRAFI (USG) MENGGUNAKAN METODE MEDIAN FILTER - Wati, Fadila (JURIKOM (Jurnal Riset Komputer), 2018)
A data or information is presented not only in the form of text data but also can be in the form of audio, video, and images. In this day and age information is very important and necessary, as is the information contained in the image. Image (image) or other terms for images is one of the multimedia components that play an important role as a form of visual information. Compared to text data, images have a lot of information. In digital formatted images damage often occurs which is defined as noise. But sometimes images can also experience a decrease, namely degradation or deterioration in quality caused by noise / noise, too contrasting colors, blurring, and others. There are several types of noise in image processing, one of which is Salt & Pepper noise. The Salt & Pepper Noise is shaped like black and white spots on the image. To reduce this noise, a method is needed, one of which is the median filter. The method used in this study is the median filter.